UTILIZING THEORY OF CHANGE IN DESIGNING IMPACTFUL SOCIAL AND EDUCATIONAL PROGRAMS - Setioko, Wahyu; Wangsanata, Victoria Carolyn (Bina Nusantara University, 2025)
The Theory of Change (ToC) is a critical tool for nonprofit organizations and philanthropic entities. ToC provides a structured approach to designing, monitoring, and evaluating social change initiatives. This study focuses on a community development activity aimed at building the capacity of Creative Commons Indonesia (CCID) and Wikimedia Indonesia (WMID) through a ToC training. The training employed the Service Learning (SL) method, which emphasizes practical application and community interaction. Seven participants engaged in a comprehensive program that included pre- and post-tests, presentations, group discussions, case studies, and practical exercises. Evaluation through paired t-tests revealed a significant increase in participants’ understanding, with pre-test scores (M = 6.14) rising to post-test scores (M = 8.86). Participants successfully developed structured ToC frameworks for their projects, demonstrating their enhanced capability to design effective social and educational interventions. The success of the training underscores the value of ToC in program planning and evaluation, contributing to more sustainable and effective social and educational programs.